Impact on clinical outcomes of right ventricular response to percutaneous correction of secondary mitral regurgitation. (8th February 2021) - Caiffa, T; Castrichini, M; Biagini, E; De Luca, A; Compagnone, M; Berardini, A; Merlo, M; Fabris, E; Vitrella, G; Pinamonti, B; Korcova, R; Barbati, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Right ventricular function (RVF) is a strong determinant of prognosis in patients with reduced ejection fraction heart failure (HFrEF) and secondary mitral regurgitation (SMR). Percutaneous mitral valve repair (pMVR) can promote the recovery of RVF. Purpose. We sought to characterize the RV response to pMVR in HFrEF with SMR and to assess the influence of improved RVF after pMVR in this specific setting of patients. Methods. We included all the patients with HFrEF and SMR≥3+ successfully treated with pMVR between April 2012 and January 2020 in two tertiary care centers for HF. Improved RVF was defined as DRVFAC≥5% at early follow-up (median time 4 months). The primary endpoint was a composite of death/heart transplant (D/HT). Results. In total, 110 patients were included. Mean age was 67 ± 12 years, mean LVEF was 31 ± 8% and mean RVFAC was 31 ± 10%. DRVFAC≥5% occurred in 54 (49%) patients and was independent from the measures of left ventricle recovery. During a median follow-up of 36 months (IQR 19-52), 40 patients (36%) died or were transplanted. After adjustment for other significant covariates, DRVFAC≥5% was significantly associated with lower risk of D/HT (HR 0.49, 95% CI 0.24 – 0.98 p < 0.042) along with M2+ at follow-up (HR 0.36; 95% CI 0.17-0.74 p 0.005). Conclusions. In patients with HFrEF and SMR, the improvement of RVF is frequent after pMVR and is associated with better long-term survival free from HT.